TRANSFORMASI PENDIDIKAN BERBASIS TEKNOLOGI: PERAN ARTIFICIAL INTELLIGENCE DAN INTERNET OF THINGS DALAM PEMBELAJARAN - Brayend Yosua Konoralma; Samsuriah (PROGRESS, 2024)
Artificial Intelligence (AI) has had a significant impact on the world of education, especially in improving the quality of learning and administrative efficiency. This study aims to analyze the main benefits of AI in education, including personalization of learning, efficiency of administrative processes, and accessibility to educational resources. Through a literature study approach. In addition, AI enables the development of virtual tutors, learning chatbots, and other technologies that provide flexibility in supporting independent learning. This technology also improves the efficiency of educational administration, such as automated assessment and student data management. Despite its many benefits, the application of AI faces challenges such as technological gaps and data privacy. With its great potential, AI is expected to continue to develop as an innovative solution to create inclusive, adaptive, and sustainable education.